Some interesting notes on the Andrena species in Slovenia (Hymenoptera: Andrenidae) - Gogala, Andrej (Acta entomologica slovenica (Ljubljana), 2011)
Notes on the distribution and behaviour of seven Andrena species in Slovenia are presented, among them the first record of Andrena nuptialis, while A. alutacea had been distinguished from A. proxima.
Keywords: Andrena; Andrenidae; entomologija; entomology; fauna; favna; Hymenoptera; Slovenia; Slovenija